2012
DOI: 10.1016/j.bbrc.2012.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte-specific ablation of Osterix leads to impaired endochondral ossification

Abstract: Osterix (Osx) is an essential transcription factor required for osteoblast differentiation during both intramembranous and endochondral ossification. Endochondral ossification, a process in which bone formation initiates from a cartilage intermediate, is crucial for skeletal development and growth. Osx is expressed in differentiating chondrocytes as well as osteoblasts during mouse development, but its role in chondrocytes has not been well studied. Here, the in vivo function of Osx in chondrocytes was examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 22 publications
3
49
0
1
Order By: Relevance
“…S9). Although the ectopic cartilage observed in mouse osx mutants (Oh et al, 2012) could be a consequence of delayed Osx-controlled perichondral ossification, we suggest that osx is dispensable for chondrocyte maturation in medaka.…”
Section: Osx In Vertebratesmentioning
confidence: 67%
See 1 more Smart Citation
“…S9). Although the ectopic cartilage observed in mouse osx mutants (Oh et al, 2012) could be a consequence of delayed Osx-controlled perichondral ossification, we suggest that osx is dispensable for chondrocyte maturation in medaka.…”
Section: Osx In Vertebratesmentioning
confidence: 67%
“…Thus, in this respect, medaka osx mutants recapitulate bone formation and mineralization defects reported in mouse mutants (Nakashima et al, 2002), confirming that osx is a crucial player in bone formation in non-mammalian vertebrates. However, unlike in the mouse model (Oh et al, 2012), the formation of cartilage appeared to be normal in medaka osx mutants (Fig. S9).…”
Section: Osx In Vertebratesmentioning
confidence: 80%
“…In our breeding experiments, we used Osx-Cre and Col2a1-Cre transgenic lines to either ablate Smpd3 in both late differentiation-stage chondrocytes and osteoblasts or just in chondrocytes, respectively. Although OSX was initially identified to be an osteoblastspecific transcription factor, more recent works have demonstrated that it is also expressed in the late-stage chondrocytes (14,32,33). The expression of OSX in the mineralizing cell types of the developing skeleton justifies the use of the Osx-Cre line in our breeding experiments that aimed to verify our original hypothesis that SMPD3 has a nonsystemic role in the skeletal tissues.…”
Section: Discussionmentioning
confidence: 87%
“…5G,H). Similarly, expression analysis of early markers of osteogenic and chondrogenic differentiation revealed that the transcription factors Runx2 and Osterix (Sp7 -Mouse Genome Informatics), as well as the osteoblast marker alkaline phosphatase (ALP) (Nishimura et al, 2012;Oh et al, 2012), were significantly downregulated in Ezh2 cko compared with control BA1, as shown by quantitative RT-PCR (Fig. 5I).…”
Section: Ezh2 Promotes Bone and Cartilage Formation In Cnccs By Reprementioning
confidence: 82%